Evaluation of a Bispidine‐Based Chelator for Gallium‐68 and of the Porphyrin Conjugate as PET/PDT Theranostic Agent. Issue 34 (20th May 2020) - Price, Thomas W.; Yap, Steven Y.; Gillet, Raphaël; Savoie, Huguette; Charbonnière, Loïc J.; Boyle, Ross W.; Nonat, Aline M.; Stasiuk, Graeme J.
Abstract: In this study a bispidine ligand has been applied to the complexation of gallium(III) and radiolabelled with gallium‐68 for the first time. Despite its 5‐coordinate nature, the resulting complex is stable in serum for over two hours, demonstrating a ligand system well matched to the imaging window of gallium‐68 positron emission tomography (PET). To show the versatility of the bispidine ligand and its potential use in PET, the bifunctional chelator was conjugated to a porphyrin, producing a PET/PDT‐theranostic, which showed the same level of stability to serum as the non‐conjugated gallium‐68 complex. The PET/PDT complex killed >90 % of HT‐29 cells upon light irradiation at 50 μm . This study shows bispidines have the versatility to be used as a ligand system for gallium‐68 in PET. Abstract : Go, go Gallium ! In this study, a bispidine ligand has been applied to the complexation of gallium(III) and radiolabelled with gallium‐68 for the first time. The resulting complex is stable in serum for over two hours, showing a ligand system perfectly matched to the imaging window of PET. To show the versatility of ligand the bifunctional chelator was conjugated to porphyrin, producing a PET/PDT‐theranostic. This killed >90 % of HT‐29 cells upon light irradiation at 100 μm .